A modified polyketone material for plastic spring and preparation method thereof
By using modified polyketone materials and composite modified fillers in plastic springs, the shortcomings of existing plastic springs in temperature resistance, strength and impact resilience are solved, and higher durability and impact resistance are achieved.
Patent Information
- Application Number
- CN202411571316.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The temperature resistance and strength of existing plastic springs are limited compared to metal springs, and there are shortcomings in impact and rebound.
Modified polyketone materials are prepared by adding polytetrafluoroethylene, suitable compatibility agents, and controlling the ratio of polyketone resin, and adding composite modified fillers to the material to improve the impact and wear resistance of the material.
It significantly improves the impact rebound and durability of plastic springs, can withstand more than 3,000 rebounds, and improves the impact strength and wear stability of the material.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and particularly relates to a modified polyketone material for plastic springs and a preparation method thereof. Background Art
[0002] Using plastic springs to replace metal springs in plastic packaging bottles can not only reduce costs, but also be more convenient to use. It can effectively avoid the problem of metal springs contaminating the products in the bottle due to rust during use. At the same time, the use of plastic springs can also facilitate the subsequent recycling and recycling of plastic packaging bottles. Plastic springs are usually made of high-strength plastics, including polyamide, polyketone, polycarbonate, etc., and have unique advantages that traditional metal springs cannot match. For example, they are lightweight, corrosion-resistant, have good insulation properties, and can maintain stable elasticity and reliability in a variety of environments. Plastic springs can be roughly divided into three types: compression springs, tension springs, and torsion springs. Compression springs are compressed from both ends under the action of force, tension springs are stretched from both ends under the action of force, and torsion springs are elastically deformed by being rotated. The appropriate spring type can be selected according to different use environments. Plastic springs are widely used in daily chemical packaging, automotive accessories, medical devices, electronic products and other fields. Their manufacturing processes are diverse, including injection molding, extrusion and winding, so that plastic springs can maintain good elasticity while meeting diverse design and functional requirements.
[0003] Although the temperature resistance and strength of plastic springs are relatively limited compared to metal springs, with the advancement of related material technology, their performance is also constantly improving, and plastic springs are gradually becoming an indispensable elastic element in daily life and modern industry. For example, Chinese patent CN111793345A discloses a plastic spring and its preparation method and application, the preparation method comprising the following steps: mixing polycarbonate, epoxy resin, modified silane coupling agent and ABS resin and adding them to an extruder for extrusion, the plastic spring can be used in the square gun sprayer of the cosmetic container, the patent uses polycarbonate, epoxy resin and ABS to improve the high temperature resistance of the material, the raw materials used are non-toxic and environmentally friendly, which can not only ensure the safety of the material in the field of daily necessities, but also ensure the durability of the material for long-term use. Chinese patent CN114941671A also discloses a plastic spring and its preparation method and application. The raw materials for preparing the plastic spring include: polyolefin, whisker silicon, maleic anhydride grafted polypropylene, nucleating agent 2-mercaptobenzimidazole, antioxidant and lubricant ethylene bis stearamide. This patent makes the plastic spring have good resilience and durability through the selection of plastic spring materials and the design of spring structure. When it is used in plastic packaging bottles, the recycling convenience and environmental protection of plastic bottles are improved. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides a modified polyketone material for plastic springs and a preparation method thereof. The present invention adds polytetrafluoroethylene and a suitable compatibilizer and controls the ratio of the polyketone resin so that the obtained modified polyketone material has good mechanical properties such as tensile strength, bending strength and impact strength, thereby improving the impact resilience and durability of the plastic spring.
[0005] The technical solution adopted by the present invention is:
[0006] A modified polyketone material for plastic springs, comprising the following raw materials:
[0007] Polyketone resin, polyetherimide, compatibilizer, polytetrafluoroethylene powder, lubricant, antioxidant.
[0008] Preferably, a modified polyketone material for a plastic spring comprises the following raw materials in parts by weight:
[0009] 75-85 parts by weight of polyketone resin, 10-20 parts by weight of polyetherimide, 3-4 parts by weight of compatibilizer, 0.6-1 parts by weight of polytetrafluoroethylene powder, 1-1.6 parts by weight of lubricant, and 0.4-0.5 parts by weight of antioxidant.
[0010] Preferably, the compatibilizer is one or a mixture of two or more of SEBS-g-MAH, POE-g-MAH and SMA.
[0011] Preferably, the compatibilizer is SEBS-g-MAH.
[0012] Preferably, the lubricant is one or a mixture of two or more of glyceryl stearate, calcium stearate, pentaerythritol stearate, ethylene bisstearamide, Fischer-Tropsch wax, EVA wax, and PE wax.
[0013] Preferably, the lubricant is a mixture of Fischer-Tropsch wax and glyceryl stearate.
[0014] Preferably, the weight ratio of the Fischer-Tropsch wax to glyceryl stearate is 1-2:1.
[0015] Preferably, the weight ratio of the Fischer-Tropsch wax to glyceryl stearate is 1:1.
[0016] Preferably, the antioxidant is selected from one or a mixture of two or more of antioxidant 1010, antioxidant 1790, antioxidant 164, antioxidant 1076, antioxidant 264, antioxidant CA, antioxidant DNP, antioxidant TPP, and antioxidant MB.
[0017] Preferably, the raw materials of the modified polyketone material for plastic springs also include: composite modified filler.
[0018] Preferably, the raw materials of the modified polyketone material for plastic springs further include: 5-8 parts by weight of composite modified filler.
[0019] Preferably, the preparation method of the composite modified filler is:
[0020] X1. Alumina nanofibers are added to the nanocellulose aqueous dispersion, mixed evenly, sonicated, filtered, freeze-dried, and then calcined to obtain alumina composite aerogel;
[0021] X2: N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, fatty alcohol polyoxyethylene ether and water are uniformly mixed, and then aramid nanofibers are added, stirred, filtered and freeze-dried to obtain pretreated aramid nanofibers;
[0022] X3: Add liquid polyester resin to dimethyl sulfoxide and mix evenly, then add the pretreated aramid nanofibers and stir, then add the alumina composite aerogel and continue stirring, filter and vacuum dry to obtain the composite modified filler.
[0023] The present invention further improves the impact strength stability and wear resistance stability of the modified polyketone material by adding a composite modified filler, so that the service life of the plastic spring is greatly improved. In the preparation of the composite modified filler, nanocellulose is overlapped with each other in the alumina aerogel structure, and after a freeze-drying process, the alumina nanofibers and nanocellulose are first gathered between ice crystals during freezing, and then the ice crystals are directly sublimated and removed during freeze-drying, thereby forming a porous structure inside the aerogel, and in addition, the nanocellulose is self-assembled into a mesh structure overlapped on the alumina nanofibers through hydrogen bonding, and then high-temperature calcination is performed to obtain an alumina composite aerogel, the composite aerogel uses the alumina nanofibers as a supporting structure, and the carbon fibers formed by high-temperature carbonization of the nanocellulose form a composite network structure, this structure significantly improves the stability of the aerogel, has excellent anti-bending and anti-compression properties, and can effectively improve the impact strength stability of the modified polyketone material.
[0024] Aramid nanofiber is a synthetic fiber composed of aromatic polyamide molecules, and has the advantages of high strength, high modulus, high temperature resistance, good dimensional stability, etc. The invention treats the aramid nanofiber with N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane in a wet state, so that the optimization effect is better, and the silanol generated by hydrolysis is combined with the surface of the nanofiber, so that the interface bonding performance between the fiber and the liquid polyester resin is improved. In addition, fatty alcohol polyoxyethylene ether is used as an auxiliary agent to make N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane fully dispersed in the solvent, ensuring that the fiber surface is fully in contact with it; using the high modulus and high stability of the aramid nanofiber and the good elasticity and wear resistance of the liquid polyester resin, the pretreated aramid nanofiber is bonded to the surface of the alumina composite aerogel by using the liquid polyester resin as a binder, so as to enhance the structural stability, form a composite modified filler, and further improve the impact strength stability and wear resistance stability.
[0025] Preferably, the preparation method of the composite modified filler is:
[0026] X1. Add 10-15 parts by weight of alumina nanofibers to 40-60 parts by weight of nanocellulose aqueous dispersion, mix evenly, sonicate, filter, freeze-dry, and then calcine to obtain alumina composite aerogel;
[0027] X2: 2-4 parts by weight of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, 0.1-0.3 parts by weight of fatty alcohol polyoxyethylene ether and 100-150 parts by weight of water are uniformly mixed, and then 15-20 parts by weight of aramid nanofibers are added, stirred, filtered and freeze-dried to obtain pretreated aramid nanofibers;
[0028] X3 Add 1-2 parts by weight of liquid polyester resin to 50-70 parts by weight of dimethyl sulfoxide and mix evenly, then add 3-5 parts by weight of the above-mentioned pretreated aramid nanofibers, stir, then add 10-15 parts by weight of the above-mentioned alumina composite aerogel and continue stirring, filter and vacuum dry to obtain the composite modified filler.
[0029] Preferably, the concentration of the nanocellulose aqueous dispersion in step 1 is 1-3 wt %.
[0030] Preferably, the ultrasonic conditions in step 1 are: ultrasonication at 100-300W, 30-50kHz for 40-60min.
[0031] Preferably, the calcination conditions in step 1 are: calcination in a nitrogen atmosphere at 800-900° C. for 100-200 min.
[0032] Preferably, the stirring conditions in step 2 are: stirring at 50-100 rpm and 30-40° C. for 30-50 min.
[0033] Preferably, the fatty alcohol polyoxyethylene ether in step 2 is fatty alcohol polyoxyethylene ether AEO-3.
[0034] Preferably, the liquid polyester resin in step 3 is an elastic polyester resin with a solid content of 88-92% and a molecular weight of 1000-1200.
[0035] Preferably, the stirring conditions in step 3 are: stirring at 50-100 rpm and 30-40° C. for 20-30 min.
[0036] Preferably, the stirring time in step 3 is 30-40 minutes.
[0037] In a specific implementation manner, the polyketone resin is an aliphatic polyketone POK produced by POKETONE (Korea Hyosung) with a brand name of M630A.
[0038] In a specific embodiment, the polyetherimide is PEI produced by SABIC (SABIC), with the brand name ULTEM1000.
[0039] In a specific embodiment, SEBS-g-MAH has a melt index of 3 g / 10 min (190° C., 2.16 kg) and a grafting rate of 1-2%.
[0040] In a specific embodiment, the polytetrafluoroethylene powder has a particle size of 200 μm and a specific gravity of 2.2 g / cm 3 , apparent density 0.52g / cm 3 .
[0041] In a specific embodiment, glyceryl stearate, CAS: 11099-07-3.
[0042] In a specific embodiment, the alumina nanofibers have a diameter of 4-8 nm and a length of 200-300 nm.
[0043] In a specific embodiment, the nanocellulose has a diameter of 15-25 nm and a length of 200-300 nm.
[0044] In a specific embodiment, the aramid nanofiber adopts the para-aramid nanofiber produced by Shandong Jufang New Materials Co., Ltd., with a diameter of 10-100 nm and an aspect ratio of 3000.
[0045] In a specific implementation manner, the liquid polyester resin uses F1190 elastic resin produced by Shenzhen Feiyang Junyan New Materials Co., Ltd., with a solid content of 88-92% and a molecular weight of 1000-1200.
[0046] The present invention also provides a method for preparing a modified polyketone material for a plastic spring, comprising the following steps:
[0047] According to the formula, polyketone resin, polyetherimide, composite modified filler, compatibilizer, polytetrafluoroethylene powder, lubricant and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 100-300 rpm to obtain the modified polyketone material for the plastic spring.
[0048] The present invention also provides a plastic spring made of the modified polyketone material for plastic springs, which comprises an upper mounting frame, an elastic member and a lower mounting frame in sequence, wherein the elastic member can be an elastic rib or a bellows with a spiral structure. The plastic spring can be applied to ordinary packaging bottles and plastic vacuum bottles after injection molding, and the plastic spring is installed on the pressing assembly of the plastic bottle when in use.
[0049] Beneficial effects of the present invention: The modified polyketone material for plastic springs prepared by the present invention has good mechanical properties such as tensile strength, bending strength and impact strength by adding polytetrafluoroethylene and a suitable compatibilizer and controlling the ratio of the polyketone resin, thereby improving the impact resilience and durability of the plastic spring, and can withstand more than 3,000 rebounds. DETAILED DESCRIPTION
[0050] The above content of the present invention is further described in detail below in conjunction with specific implementation modes, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments.
[0051] Example 1
[0052] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0053] 75 parts by weight of polyketone resin, 20 parts by weight of polyetherimide, 3 parts by weight of SEBS-g-MAH, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0054] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0055] According to the formula, polyketone resin, polyetherimide, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0056] Example 2
[0057] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0058] 75 parts by weight of polyketone resin, 18 parts by weight of polyetherimide, 4 parts by weight of SEBS-g-MAH, 1 part by weight of polytetrafluoroethylene powder, 0.8 parts by weight of Fischer-Tropsch wax, 0.8 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0059] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0060] According to the formula, polyketone resin, polyetherimide, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0061] Example 3
[0062] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0063] 80 parts by weight of polyketone resin, 15 parts by weight of polyetherimide, 3 parts by weight of SEBS-g-MAH, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0064] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0065] According to the formula, polyketone resin, polyetherimide, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0066] Example 4
[0067] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0068] 85 parts by weight of polyketone resin, 10 parts by weight of polyetherimide, 3 parts by weight of SEBS-g-MAH, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0069] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0070] According to the formula, polyketone resin, polyetherimide, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0071] Test Example 1
[0072] The modified polyketone material for plastic springs obtained in the above Examples 1-4 was tested for mechanical properties. The test results are shown in Table 1.
[0073] Table 1 Mechanical properties of modified polyketone materials
[0074] Test Standards Example 1 Example 2 Example 3 Example 4 Tensile strength / Mpa ASTM D-638 66 65 62 59 Bending strength / Mpa ASTM D-790 70 68 65 62 Flexural modulus / Mpa ASTM D-790 1460 1400 1350 1310 <![CDATA[Izod impact strength KJ / m 2 > GB / T-1843 13.5 12.8 12.0 11.7
[0075] Comparative Example 1
[0076] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0077] 75 parts by weight of polyketone resin, 23 parts by weight of polyetherimide, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0078] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0079] According to the formula, polyketone resin, polyetherimide, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0080] Comparative Example 2
[0081] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0082] 70 parts by weight of polyketone resin, 25 parts by weight of polyetherimide, 3 parts by weight of SEBS-g-MAH, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0083] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0084] According to the formula, polyketone resin, polyetherimide, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0085] Comparative Example 3
[0086] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0087] 85 parts by weight of polyketone resin, 10.6 parts by weight of polyetherimide, 3 parts by weight of SEBS-g-MAH, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0088] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0089] According to the formula, polyketone resin, polyetherimide, SEBS-g-MAH, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0090] Test Example 2
[0091] The modified polyketone material for plastic springs obtained in the above-mentioned Examples 1-4 and Comparative Examples 1-3 was tested for resilience performance. The test results are shown in Table 2.
[0092] Table 2 Resilience properties of modified polyketone materials
[0093] Continuous impact rebound times Example 1 3800 Example 2 3500 Example 3 3300 Example 4 3100 Comparative Example 1 1000 Comparative Example 2 2300 Comparative Example 3 2600
[0094] It can be seen from the test results that compared with Examples 1-4, Comparative Example 1 did not add SEBS-g-MAH, resulting in a poor rebound number of the polyketone material; Comparative Example 2 reduced the proportion of polyketone in the matrix to 70%, resulting in a rebound number of less than 3000 times; Comparative Example 3 did not add polytetrafluoroethylene, which affected the fatigue resistance of the material, thereby resulting in a decrease in the rebound number of the polyketone material.
[0095] Example 5
[0096] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0097] 75 parts by weight of polyketone resin, 12.5 parts by weight of polyetherimide, 7.5 parts by weight of composite modified filler, 3 parts by weight of SEBS-g-MAH, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0098] The preparation method of the composite modified filler is:
[0099] 12 parts by weight of alumina nanofibers were added to 50 parts by weight of 2.5 wt% nanocellulose aqueous dispersion and mixed evenly, ultrasonicated at 200 W and 35 kHz for 50 min, filtered and freeze-dried, and then calcined at 850 ° C for 150 min in a nitrogen atmosphere to obtain an alumina composite aerogel;
[0100] 3 parts by weight of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, 0.2 parts by weight of fatty alcohol polyoxyethylene ether AEO-3 and 120 parts by weight of water were uniformly mixed, and then 18 parts by weight of aramid nanofibers were added, stirred at 60 rpm and 35° C. for 40 minutes, filtered and freeze-dried to obtain pretreated aramid nanofibers;
[0101] 1.5 parts by weight of liquid polyester resin were added to 60 parts by weight of dimethyl sulfoxide and mixed evenly, then 4 parts by weight of the pretreated aramid nanofibers were added, stirred at 60 rpm and 35° C. for 25 minutes, then 11.5 parts by weight of the alumina composite aerogel were added and stirred for 35 minutes, filtered and vacuum dried to obtain the composite modified filler.
[0102] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0103] According to the formula, polyketone resin, polyetherimide, composite modified filler, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0104] Example 6
[0105] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0106] 75 parts by weight of polyketone resin, 12.5 parts by weight of polyetherimide, 7.5 parts by weight of composite modified filler, 3 parts by weight of SEBS-g-MAH, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0107] The preparation method of the composite modified filler is:
[0108] 12 parts by weight of alumina nanofibers were added to 50 parts by weight of 2.5 wt% nanocellulose aqueous dispersion and mixed evenly, ultrasonicated at 200 W and 35 kHz for 50 min, filtered and freeze-dried, and then calcined at 850 ° C for 150 min in a nitrogen atmosphere to obtain an alumina composite aerogel;
[0109] 1.5 parts by weight of liquid polyester resin were added to 60 parts by weight of dimethyl sulfoxide and mixed evenly, then 4 parts by weight of aramid nanofibers were added, stirred at 60 rpm and 35° C. for 25 minutes, then 11.5 parts by weight of the above-mentioned alumina composite aerogel were added and stirred for 35 minutes, filtered and vacuum dried to obtain the composite modified filler.
[0110] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0111] According to the formula, polyketone resin, polyetherimide, composite modified filler, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0112] Example 7
[0113] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0114] 75 parts by weight of polyketone resin, 12.5 parts by weight of polyetherimide, 7.5 parts by weight of composite modified filler, 3 parts by weight of SEBS-g-MAH, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0115] The preparation method of the composite modified filler is:
[0116] 3 parts by weight of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, 0.2 parts by weight of fatty alcohol polyoxyethylene ether AEO-3 and 120 parts by weight of water were uniformly mixed, and then 18 parts by weight of aramid nanofibers were added, stirred at 60 rpm and 35° C. for 40 minutes, filtered and freeze-dried to obtain pretreated aramid nanofibers;
[0117] 1.5 parts by weight of liquid polyester resin are added to 60 parts by weight of dimethyl sulfoxide and mixed evenly, then 4 parts by weight of the above-mentioned pretreated aramid nanofibers are added, stirred at 60 rpm and 35°C for 25 minutes, then 11.5 parts by weight of alumina nanofibers are added and stirred for 35 minutes, filtered and vacuum dried to obtain the composite modified filler.
[0118] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0119] According to the formula, polyketone resin, polyetherimide, composite modified filler, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0120] Example 8
[0121] A modified polyketone material for plastic springs is prepared from the following raw materials:
[0122] 75 parts by weight of polyketone resin, 12.5 parts by weight of polyetherimide, 7.5 parts by weight of composite modified filler, 3 parts by weight of SEBS-g-MAH, 0.6 parts by weight of polytetrafluoroethylene powder, 0.5 parts by weight of Fischer-Tropsch wax, 0.5 parts by weight of glyceryl stearate, and 0.4 parts by weight of antioxidant 1076.
[0123] The preparation method of the composite modified filler is:
[0124] 12 parts by weight of alumina nanofibers were added to 50 parts by weight of 2.5 wt% nanocellulose aqueous dispersion and mixed evenly, ultrasonicated at 200 W and 35 kHz for 50 min, filtered and freeze-dried, and then calcined at 850 ° C for 150 min in a nitrogen atmosphere to obtain an alumina composite aerogel;
[0125] 3 parts by weight of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, 0.2 parts by weight of fatty alcohol polyoxyethylene ether AEO-3 and 120 parts by weight of water were uniformly mixed, and then 18 parts by weight of aramid nanofibers were added, stirred at 60 rpm and 35° C. for 40 minutes, filtered and freeze-dried to obtain pretreated aramid nanofibers;
[0126] 4 parts by weight of the pretreated aramid nanofibers were added to 60 parts by weight of dimethyl sulfoxide and mixed evenly. The mixture was stirred at 60 rpm and 35° C. for 25 minutes. Then 11.5 parts by weight of the alumina composite aerogel were added and stirred for 35 minutes. The mixture was filtered and vacuum dried to obtain the composite modified filler.
[0127] A method for preparing a modified polyketone material for a plastic spring comprises the following steps:
[0128] According to the formula, polyketone resin, polyetherimide, composite modified filler, SEBS-g-MAH, polytetrafluoroethylene powder, Fischer-Tropsch wax, glyceryl stearate and antioxidant are uniformly mixed, and granulated by extrusion in a twin-screw extruder at an extrusion temperature of 220-250° C. and a screw speed of 200 rpm to obtain the modified polyketone material for the plastic spring.
[0129] Test Example 3
[0130] The modified polyketone material for plastic spring obtained in the above embodiment was tested by using an MMS-2A multifunctional friction and wear testing machine with reference to the method in GB T 3960-2016. A dry friction test was performed at 23° C. and 50% relative humidity to determine the friction coefficient.
[0131] Table 3 Wear resistance of modified polyketone materials
[0132] Friction coefficient Example 1 0.41 Example 5 0.19 Example 6 0.28 Example 7 0.30 Example 8 0.24
[0133] Test Example 4
[0134] Under the conditions of 90°C and 95% relative humidity, the modified polyketone material for plastic spring obtained in the above embodiment was placed in a constant temperature and humidity chamber for 2 months, and then the impact strength was measured, and then compared with the initial impact strength, and the impact strength retention rate was calculated to reflect the durability of the material. Impact strength retention rate = (initial impact strength - impact strength after 2 months) / initial impact strength × 100%.
[0135] Table 4. Stability of modified polyketone materials
[0136] Impact strength retention Example 1 79.0% Example 5 96.3% Example 6 90.5% Example 7 87.8% Example 8 92.1%
[0137] It can be seen from the test results that the modified polyketone material for the plastic spring prepared by the present invention significantly improves the wear resistance and impact stability of the polyketone material by adding a specific composite modified filler. This is because the composite modified filler used in the present invention utilizes nanocellulose to overlap each other in the alumina aerogel structure, firstly aggregating the alumina nanofibers and nanocellulose between ice crystals during freezing, and then directly sublimating and removing the ice crystals during freeze-drying, thereby forming a porous structure inside the aerogel. The composite aerogel uses alumina nanofibers as a supporting structure, and forms a composite network structure with carbon fibers formed by high-temperature carbonization of nanocellulose. This structure significantly improves the stability of the aerogel, has excellent bending and compression resistance, and can effectively improve the impact strength stability of the modified polyketone material; further, the present invention uses N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane in a wet state. The aramid nanofibers are treated, and the silanol generated by hydrolysis is combined with the surface of the nanofibers, so that the interfacial bonding performance between the fibers and the liquid polyester resin is improved. In addition, fatty alcohol polyoxyethylene ether is used as an auxiliary agent to fully disperse N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane in the solvent to ensure that the fiber surface is fully in contact with it; utilizing the high modulus and high stability of the aramid nanofibers and the good elasticity and wear resistance of the liquid polyester resin, the liquid polyester resin is used as a binder to bond the pretreated aramid nanofibers to the surface of the alumina composite aerogel, thereby enhancing the structural stability, forming a composite modified filler, and further improving the impact strength stability and wear resistance stability.
[0138] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A modified polyketone material for a plastic spring, characterized in that: Including the following ingredients: 75-85 parts by weight of polyketone resin, 10-20 parts by weight of polyetherimide, 3-4 parts by weight of compatibilizer, 0.6-1 parts by weight of polytetrafluoroethylene powder, 1-1.6 parts by weight of lubricant, and 0.4-0.5 parts by weight of antioxidant; the compatibilizer is SEBS-g-MAH.
2. The modified polyketone material for plastic springs according to claim 1, characterized in that: The lubricant is one or a mixture of two or more of glyceryl stearate, calcium stearate, pentaerythritol stearate, ethylene bis stearamide, Fischer-Tropsch wax, EVA wax and PE wax.
3. The modified polyketone material for plastic springs according to claim 2, characterized in that: The lubricant is a mixture of Fischer-Tropsch wax and glyceryl stearate.
4. The modified polyketone material for plastic springs according to claim 1, characterized in that: The antioxidant is selected from one or a mixture of two or more of antioxidant 1010, antioxidant 1790, antioxidant 164, antioxidant 1076, antioxidant 264, antioxidant CA, antioxidant DNP, antioxidant TPP, and antioxidant MB.
5. The modified polyketone material for plastic springs according to claim 1, characterized in that: The raw materials of the modified polyketone material for plastic springs also include: composite modified filler.
6. The modified polyketone material for plastic springs according to claim 5, characterized in that: The preparation method of the composite modified filler is: X1. Alumina nanofibers are added to the nanocellulose aqueous dispersion, mixed evenly, sonicated, filtered, freeze-dried, and then calcined to obtain alumina composite aerogel; X2: N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, fatty alcohol polyoxyethylene ether and water are uniformly mixed, and then aramid nanofibers are added, stirred, filtered and freeze-dried to obtain pretreated aramid nanofibers; X3: Add liquid polyester resin to dimethyl sulfoxide and mix evenly, then add the pretreated aramid nanofibers and stir, then add the alumina composite aerogel and continue stirring, filter and vacuum dry to obtain the composite modified filler.
7. The method for preparing a modified polyketone material for a plastic spring according to claim 1, characterized in that: The following steps are involved: The polyketone resin, polyetherimide, compatibilizer, polytetrafluoroethylene powder, lubricant and antioxidant are uniformly mixed according to the formula, and granulated by extrusion in a twin-screw extruder to obtain the modified polyketone material for the plastic spring.
Citation Information
Patent Citations
Plastic spring and preparation method and application thereof
CN111793345A
Plastic spring and preparation method and application thereof
CN114941671A
Thermoplastic elastomer gasket material and production method thereof
CN107513263A
Poly(ether ketone ketone) / fusible fluoroplastic alloy and preparation method thereof
CN107880523A